Exploring the causes of adverse events in NHS hospital practice. - Neale, G; Woloshynowych, M; Vincent, C (2001)
In a previous paper we reported that 10.8% of patients admitted to two large hospitals in Greater London experienced one or more adverse events, of which half were deemed preventable. Here we examine the underlying causes of errors in clinical practice. Rather than identifying specific errors made by individuals, we have looked at possible faults in the organization of care. Adverse events were grouped according to stages in the care process: diagnosis, preoperative assessment and care, operative or invasive procedure (including anaesthesia), ward management, use of drugs and intravenous fluids and discharge from hospital. Less than 20% of preventable adverse events were directly related to surgical operations or invasive procedures and less than 10% to misdiagnoses. 53% of preventable adverse events occurred in general ward care (including initial assessment and the use of drugs and intravenous fluids) and 18% in care at the time of discharge. Probable contributory factors in these errors included dependence on diagnoses made by inexperienced clinicians, poor records, poor communication between professional carers, inadequate input by consultants into day-to-day care, and lack of detailed assessment of patients before discharge.